Diseño y operacionalización del manual de procedimiento para los procesos de registro único de contribuyentes - Páez Velepucha, Silvana del Carmen (2008)
This paper aims to present an example of design and operability must have a procedures manual processes any area or department of the Internal Revenue Service, based on international models, user roles, processes and hierarchies preset Institution.